2007
DOI: 10.1007/s11434-007-0480-x
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein expression induced by nickel accumulation in the midgut of Spodoptera litura Fabricius larvae exposed to nickel

Abstract: Metallothionein expression induced by nickel accumulation in the midgut of Spodoptera litura Fabricius larvae was investigated by exposing S. litura larvae to the artificial diets amended with different doses of nickel for 3 generations. Nickel accumulations in the midgut of 6th instar larvae were detected by Inductively Coupled Plasma-Atomic Emission Spectrometer (ICP-AES), and the induced metallothionein expression in the midgut of 5th and 6th instar larvae in 120 h were quantified using cadmium-hemoglobin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It was also proposed that GSH is capable of chelating metals soon after they enter into the cells, and transferring the metals to the metal-binding site of MT [23] . In our previous studies, heavy metal nickel was found to be able to accumulate in the midgut of the 6th instar larvae of Spodoptera litura Fabricius exposed to different doses of nickel for 3 generations [24] . Furthermore, MT increased with the increasing nickel doses in diets and the stressing time in one generation [24] .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…It was also proposed that GSH is capable of chelating metals soon after they enter into the cells, and transferring the metals to the metal-binding site of MT [23] . In our previous studies, heavy metal nickel was found to be able to accumulate in the midgut of the 6th instar larvae of Spodoptera litura Fabricius exposed to different doses of nickel for 3 generations [24] . Furthermore, MT increased with the increasing nickel doses in diets and the stressing time in one generation [24] .…”
mentioning
confidence: 91%
“…In our previous studies, heavy metal nickel was found to be able to accumulate in the midgut of the 6th instar larvae of Spodoptera litura Fabricius exposed to different doses of nickel for 3 generations [24] . Furthermore, MT increased with the increasing nickel doses in diets and the stressing time in one generation [24] . However, the trends of detoxification enzymes CarE and GST in midgut of S. litura larvae stressed by nickel, and the relationships between enzyme activities and MT levels in midgut were unknown.…”
mentioning
confidence: 91%